2008
DOI: 10.1038/ni1574
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions for the endoplasmic reticulum calcium sensors STIM1 and STIM2 in T cell activation and tolerance

Abstract: Store-operated Ca2+ entry through calcium release-activated calcium channels is the chief mechanism for increasing intracellular Ca2+ in immune cells. Here we show that mouse T cells and fibroblasts lacking the calcium sensor STIM1 had severely impaired store-operated Ca2+ influx, whereas deficiency in the calcium sensor STIM2 had a smaller effect. However, T cells lacking either STIM1 or STIM2 had much less cytokine production and nuclear translocation of the transcription factor NFAT. T cell-specific ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
789
5
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 544 publications
(856 citation statements)
references
References 69 publications
60
789
5
2
Order By: Relevance
“…Studies in mice have also led to similar conclusions. Whereas global deletion of Orai1, STIM1, or STIM2 in mice results in premature death (12,28,29), T-cell-targeted deletion of both STIM1 and STIM2 leads to autoimmune symptoms. Decreased numbers of Tregs as well as compromised suppressive function of Tregs on effector T cells were noted in these mice, suggesting that Treg development appears to be especially sensitive to the absence of STIM-dependent Ca 2+ influx (12).…”
Section: Reduction Of Stim1 and Stim2 Expression In Pbmcs From Pssmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in mice have also led to similar conclusions. Whereas global deletion of Orai1, STIM1, or STIM2 in mice results in premature death (12,28,29), T-cell-targeted deletion of both STIM1 and STIM2 leads to autoimmune symptoms. Decreased numbers of Tregs as well as compromised suppressive function of Tregs on effector T cells were noted in these mice, suggesting that Treg development appears to be especially sensitive to the absence of STIM-dependent Ca 2+ influx (12).…”
Section: Reduction Of Stim1 and Stim2 Expression In Pbmcs From Pssmentioning
confidence: 99%
“…Whereas global deletion of Orai1, STIM1, or STIM2 in mice results in premature death (12,28,29), T-cell-targeted deletion of both STIM1 and STIM2 leads to autoimmune symptoms. Decreased numbers of Tregs as well as compromised suppressive function of Tregs on effector T cells were noted in these mice, suggesting that Treg development appears to be especially sensitive to the absence of STIM-dependent Ca 2+ influx (12). It also has been demonstrated that calcineurin-NFAT signaling, which is activated by Ca 2+ entry via SOCE channels, is important for regulating Treg development and function (30,31).…”
Section: Reduction Of Stim1 and Stim2 Expression In Pbmcs From Pssmentioning
confidence: 99%
See 1 more Smart Citation
“…Stim2 fl/fl mice 25 were crossed to B6.Cg-Tg(CaMKII-Cre)T29-1Stl/J mice 26 Wilcoxon signed rank test was used for within group comparisons and Mann-Whitney-U-test, when compared between groups. Statistical significance was assumed at p < 0.05.…”
Section: Mouse Linesmentioning
confidence: 99%
“…These findings have triggered intense interest in developing specific pharmacologic inhibitors of the CRAC channel to treat a variety of autoimmune disorders. In mice, the absence of Orai1 or STIM1 function causes multiple defects of cytokine expression in T cells (interleukin (IL)-2, interferon-g, IL-4, IL-10) Oh-Hora et al 2008), and in mast cells, defective synthesis or release of inflammatory mediators (tumor necrosis factor-a, IL-6, serotonin, and leukotriene C 4 ) leads to a reduced anaphylaxis response in vivo (Baba et al 2008;Vig et al 2008). B-cell targeted deletion of STIM1 and STIM2 revealed a novel role for SOCE in enabling B cells to limit autoimmunity; in these animals reduced secretion of the anti-inflammatory cytokine IL-10 was linked to increased severity of experimental autoimmune encephalomyelitis, a model for multiple sclerosis (Matsumoto et al 2011).…”
Section: Immune Cellsmentioning
confidence: 99%